Northeastern Canada - White, James, 1863-1928
This is a general map of Northeastern Canada in 1908 showing towns, rivers, lakes, falls, rapids and seabed geology. "Accompanying Canada's Fertile Northland" Scale 1:2,217,000, or 35 miles to 1 inch. Relief shown by spot heights. Depth shown by soundings. Shows towns, rivers, lakes, falls, rapids and seabed geology. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .